The relationship between script memory for everyday events and schizotypy: an investigation through a development of Japanese Situational Feature Recognition Test - Kikutani, Mariko; Takiguchi, Yuta; Ebina, Kota; Matsui, Mie (Frontiers in Psychiatry, 2024)
Background Script memory is stored information about a sequential structure of an activity (e.g., going shopping), including what actors do, the purpose of the activity, and the likely consequences of the actor’s actions. It has been reported that script memory is impaired among schizophrenia patients. The present research investigated the relationship between schizotypal personality tendencies (schizotypy) and script memory by testing Japanese individuals. Method First, a new test to measure the intactness of the script memory was created by asking the public to report activities they often perform and what behaviors each activity contains. The test contains 15 everyday activities, each accompanied by 15 behavior choices, either strongly associated, completely unrelated, or weakly associated with the activity. Next, undergraduate participants were presented with the test and chose appropriate behaviors for each activity (Study 1 and 2). Their extent of schizotypy was measured using Schizotypal Personality Questionnaire Brief (SPQ-B). Study 3 targeted the public of various ages. In addition to Study 2 procedure, participants reported the extent of psychological burden for performing each activity, their life satisfaction, and subjective evaluation of their memory ability. Results All studies consistently found that the script memory performance was worse for individuals with higher schizotypy. Signal detection indices for accurate discrimination between correct and incorrect choices, which were A’ in Study 1 and C in Study 2 and 3, negatively correlated with the SPQ-B scores (r = -0.16, -0.11, -0.17, respectively). Study 3 found that the relationship between schizotypy and memory task performance was mediated by the extent of psychological burden. When a signal detection index (d’) for the memory task was regressed on the SPQ-B, while the psychological burden scores being a mediator, the mediation effect was significant (B = 0.003, SE = 0.001, 95% CI [0.001, 0.005]). Conclusion Individuals with higher schizotypy seem to associate unrelated behaviors to an event, forming script memory with irrelevant information, maybe due to the schizotypy symptom of having peculiar thoughts. The newly created test must be validated using a clinical population to expand its potential to be used in clinical research.